Microwave-assisted extraction and characterization of fatty acid from eel fish (Monopterus albus) - Afolabi, Haruna Kolawole; Siti Kholijah, Abdul Mudalip; Alara, Oluwaseun Ruth (Elsevier, 2018)
Eel fish (Monopterus albus) is a functional food that has shown remarkable effects on a range of diseases, which include inflammatory diseases, type 2 diabetes and cancer. This study emphasized on the use of microwaveassisted extraction (MAE) technique in studying the effects of three MAE parameters (irradiation time, microwave temperature and microwave power) to obtain extract from eel fish using ethanol as the extracting solvent. The free fatty acid (FFA), acid value, fatty acid contents, and functional groups in the extract were also examined. More so, the maximum extraction yield of 16.13% w/w was obtained at a microwave power of 800 W, FFA and acid value of 1.35 and 2.69 mg KOH/g, respectively confirmed good quality of the obtained extract. In addition, the major fatty acid contents in the extract using gas chromatography-mass spectrometry (GC-MS) analysis were arachidonic acid, linolenic acid, myristic acid, oleic acid, palmitic acid, eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA). Consequently, the Fourier transform infrared spectrometry (FTIR) analysis confirmed the presence of different functional groups in the extract. Therefore, this study divulged that MAE is an efficient and reliable technique for extracting high yields of fatty acids from M. albus fish with a notable potential for industrial applications.